Saponin Bitterness Reduction of Carica papaya Leaf Extracts through Adsorption of Weakly Basic Ion Exchange Resins - Sharifah Nuruljannah Syed Amran; Noraziani Zainal Abidin; Haslaniza Hashim; Saiful Irwan Zubairi (Journal of Food Quality, 2018)
Carica papaya that belongs to Caricaceae family has long been known as a traditional medicine for dengue fever, as well as for anticancer and antiinflammatory studies following identification of beneficial phytochemicals such as saponins in the leaves. Unfortunately, the compound has been known to induce a bitter taste in the leaf extract for human consumption, making them unpopular and nonconsumer friendly. Thus, this study aims to observe the potential adsorption of saponin compound from C. papaya leaves using ion exchange resins as an adsorbent for the reduction of bitter-taste-inducing saponins. This study uses three types of weakly basic ion exchanging resins, namely, Amberlite IRA-67, Diaion WA30, and Diaion WA21J, at different adsorbent doses of 5% (w/v) and 10% (w/v). The Peleg model suggests that the extraction of saponins from C. papaya leaves lasted for 12.50 hours yield a maximum amount of saponins, 9.31 mg/g. Further study shows that there is a significant difference (p<0.05) of saponin adsorption percentage between these three types of resins. The Diaion WA30 resin showed the highest percentage of adsorption at 87.83% (w/w) as compared to the other two 5% (w/v) loaded resin. The 10% (w/v) resin-loaded Diaion WA30 demonstrated the highest overall adsorption capacity as much as 97.59% (w/w) with the shortest exhaustive time of 4.99 hours. The overall acceptance of samples in sensory evaluation treated with ion exchange resins gave good response in which the sample treated with 10% (w/v) resin-loaded Diaion WA30 demonstrated the highest overall acceptance in parallel with having the lowest bitterness score as compared to other samples and fresh samples (untreated). The Langmuir constant (RL) was less than one (0.167–0.398), indicating the adsorption of saponins onto Diaion WA30 was favourable.